Palladium incorporated MIL-101(Cr): a heterogeneous and reusable catalyst for the C–H functionalization of unactivated arenes. (23rd November 2022) - Sarkar, Fillip Kumar; Gajurel, Sushmita; Kyndiah, Lenida; Sarkar, Rajib; Devan, Rupesh S.; Pal, Amarta Kumar
Abstract : Palladium incorporated MIL-101(Cr) as an efficient heterogeneous catalyst has been developed for the C–H functionalization of unactivated arenes. Abstract : Herein, a palladium containing metal–organic framework was designed for use in the C–H functionalization of unactivated arenes. The catalyst was prepared via post-synthetic modification of amino-functionalized MIL-101(Cr) and was well characterized using spectroscopic techniques. The catalyst is highly active in the aforementioned reaction, resulting in a 70–92% yield of the desired products at room temperature. Mild reaction conditions, gram-scale synthesis, easy recovery, and reusability of the catalyst add sustainable advantages to the protocol.